Population and labor dynamics in large informal markets: Implications for pension systems with evidence from Ecuador - Margarita Velín-Fárez (Contemporary Economics, 2021)
This paper reviews Ecuador's population structure and labor market dynamics with a focus on the causes of inequality, particularly among older adults receiving contributory pensions. This serves as a basis for characterizing the main restrictions that the Ecuadorian pension system must address. This analysis is valuable for three key reasons. First, the population structure of many less developed countries is converging toward that of developed countries, with older age groups increasing in proportion. Second, Ecuador is among the countries in Latin America and the Caribbean with the highest degree of informality in the labor market, which lowers the coverage of contributory pension schemes. Third, regarding gender inequality, the rate of women's labor participation in 2010 was among the lowest in South America. The findings suggest that a younger population structure will not be the main solution to financial problems and the pension inadequacy that are facing most pension systems worldwide. Improvements in labor market institutions are required to increase the pension system's insurance. The study concludes by discussing several proposals aimed at increasing pension coverage and reducing inequality.
Keywords: H55; J08; 330; Public pensions; Informality; Labor Markets; Latin America; Ecuador